Scurvy masquerading as IgA vasculitis - Hanna L. Kassa; S. Singh; M. Douglas-Jones; Gill Schermbrucker; J De Lange; Frank Phoya; Claire Butters; Carol Hlela; Ashton Coetzee; Ebrahim Banderker; Kate Webb (BMC, 2024)
Abstract Background Vitamin C deficiency, or scurvy, is rare but poses risks for children with poor diets, limited resources, or malabsorption issues. It may also be common in children with restrictive or selective dietary habits in children with global developmental delay, autism spectrum disorder, and physical disabilities. Symptoms include fatigue, irritability, joint and muscle pain, joint swellings, edema, swollen gums, easy bruising, and delayed wound healing. Early recognition and prompt intervention are essential to prevent the progression of symptomatic vitamin C deficiency in children. Case presentation We present a case of a 13-year-old boy with developmental delay secondary to Lennox Gastaut syndrome referred for suspected recurrent, severe, and atypical IgA vasculitis. He presented with irritability, loss of appetite, petechial and ecchymotic lower limb lesions, unilateral gum swelling, severe arthritis, peripheral oedema, severe weight loss, anaemia, and raised inflammatory markers. Multiple investigations were performed before the diagnosis of scurvy was made. A surgical finding of friable gingival tissue with multiple loose teeth, a skin biopsy with follicular hyperkeratosis and extravasated perifollicular red blood cells, and a typical X-ray finding led to the diagnosis of scurvy. Conclusion Scurvy should be given careful consideration as a differential diagnosis in patients presenting with musculoskeletal issues, mucocutaneous complaints, and constitutional symptoms such as malaise, asthenia, irritability, and loss of appetite. A focused and detailed dietary history looking for a lack of good sources of vitamin C can be an easy indicator of this differential. Imaging studies revealing the typical features can also help make the diagnosis. Pathology of the skin revealing pathognomonic features can add to the certainty of the diagnosis. In the absence of all else, the rapid response to treatment with an appropriate dose of vitamin C has a diagnostic and therapeutic role.